EFFECTS OF ECONOMIC CRISIS IN THE MUNICIPALITIES OF LITHUANIA IN CONTEXT OF THE PRINCIPLE OF RESPONSIBLE GOVERNANCE - Andruškevičius, Arvydas (Teisė, 2015)
The constitutional principle of responsible governance is equally imperative to the central governmental authorities as well as to the public administrative bodies of municipalities. The particularities of public administrative functions determine that the implementation of the discussed principle in municipalities is highly dependent on financial resources. The legislation regarding finances of the State, which were adopted at the beginning of economic recession, and their amendments, which were adopted in 2009, have limited the possibilities of municipalities to perform the obligations in the fields of public administration and provision of public services. The municipalities had prepared various instruments in order to save funds in respect to the financial crisis. These decisions of municipalities had an impact on the quality of ensuring rights and legitimate needs of both, individuals and business entities as well as public servants (e.g. recently their salaries were reduced, civil servants were offered to go on leave at their own expenses etc.).Association of Local Authorities in Lithuania has proposed a number of suggestions to the Seimas and the Government regarding solving the financial problems of municipalities in 2009 and subsequent years. Majority of such proposals had not been approved. The decisions of the central administrative bodies are difficult to assess merely from the legal point of view. On the contrary, it requires an impartial and complex analysis of various fields, the results thereof could be a ground for legal scholars and practitioners. However, it is undisputed that the interests of municipalities and the State regarding public services have to be combined even during the economic crisis.It is to be noted that not all the functions assigned to the municipalities directly depend on financial possibilities. Therefore the possibility that mandatory rules of the Law on Public Administration and other legislation are not being performed properly due to decreased motivation of public servants of municipalities to perform their duties responsibly cannot be justified. The Constitutional Court stated that higher standards are applied to public servants in comparison with other employees. The extreme conditions of economic crisis do not affect the content of the discussed constitutional doctrine.